The relationship between household gender attitudes and women’s poultry production: Evidence from Burkina Faso - Leight, Jessica; Martinez, Elena M.; Heckert, Jessica; Gelli, Aulo (International Food Policy Research Institute, 2021)
Enhancing women’s participation in agricultural production, including livestock production, has the potential to generate a range of benefits for rural households in the developing world. These benefits include enhanced economic welfare, investment in children’s health and nutrition, and empowerment for women. However, attitudes and norms may shape the ability of women to engage in a broader range of productive activities if those activities are not viewed as traditionally female domains. The attitudes of women themselves and their husbands may be particularly salient: if women do not view livestock production as an appropriate activity to pursue based on their perception of community norms, they may not be responsive to economic incentives designed to encourage their involvement. Similarly, if husbands do not view ownership and control over assets or the sale of agriculture as appropriate roles for their wives, it may be very challenging for women to maintain or increase their role in household agricultural production.